Migration intentions and motives of health workers and medical students – a country case study from Hungary - Fabula Szabolcs; Ilcsikné Makra Zsófia; Pál Viktor; Lados Gábor; Boros Lajos („RIK-U” Kft., 2020)
Abstract. The migration of health workers is a global phenomenon with considerable impact on health care systems, which issue became a policy concern in Hungary after the Eastern Enlargement of the European Union in 2000s and early 2010s. The main aim of this paper is to reveal the migration intentions and motives of Hungarian medical students and health professionals.
https://kmf.uz.ua/wp-content/uploads/2020/09/final_1_kotet-foldrajzfkonf-2020-07-14.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00008119
Keywords: health professionals; labour migration; mobility; brain drain; Hungary